EXTRACTION OF ANTHOCYANINS FROM FRUITS OF BERRIES BY ULTRASOUND ASSISTED METHOD AND QUANTIFICATION OF TOTAL MONOMERIC ANTHOCYANINS WITH SPECTROPHOTOMETRIC METHODS - Kundakci, Gulem Yoklayan; Cetin, Gulten (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Berries are a rich source of polyphenols, in particular anthocyanins and flavonols and contain relatively high amount of anthocyanins. The aim of this study is quantified of total anthocyanins in the fruits of dried cranberry, dried blueberry and fresh blueberry by new spectrofotometric techniques including the methods of absorption, first derivative absorption, difference absorption and difference first derivative absorption after extraction of anthocyanins by using ultrasonic assisted method (UAM). The acidified methanol solution was used as methanol: HCI (90:10) for extraction solvent. The optimum ratio of solid to liquid (g/mL) was found as 1/8 and 1/3 for dried blueberry and cranberry respectively. The extractions were carried out in two step as 30 min for each one in the ambient temperature. The amounts of total anthocyanin in fruits were calculated with developed spectrophotometric techniques between as 9-14 mg/100 g dried cranberry; 75-128 mg/100 g dried blueberry and 408-531 mg/100 g fresh blueberry. The developed methods were compared with official method (AOAC Official Method 2005.02). The validation studies were conducted with determination of total anthocyanin amounts in fruits for intraday and interday studies. The maximum recoveries were found between as 97.13 % and 97.84%; 98.17% and 97.09%; 98.70% and 98.07 % for intraday and interday determinations of anthocyanin in berry extracts for dried cranberry and dried blueberry and fresh blueberry respectively. While LOD is 0.21-0.95 mu g/mL; 0.41-0.86 mu g/mL and 0.52-2.20 mu g/mL LOQ is 0.70-3.15 mu g/mL; 1.36-2.87 mu g/mL and 1.75-7.33 mu g/mL for intraday studies and while LOD is 0.19-0.81 mu g/mL; 0.33-1.20 mu g/mL and 0.24-1.90 mu g/mL LOQ is 0.62-2.71 mu g/mL; 1.09-4.00 mu g/mL and 0.80-6.34 mu g/mL for interdays studies for fruits of dried cranberry, dried blueberry and fresh bluebery respectively. Standard addition methods were applied for all techniques.
Keywords: Ultrasonic assisted extraction; blueberry; cranberry; spectrofotometry; pH difference spectrofotometric method; SPECTROMETRY; Environmental Sciences & Ecology